Rehabilitation of an ocular defect with intraorbital implant and custom-made prosthesis using digital photography and gridded spectacle - Dolanchanpa Dasgupta; Kaustubh Das; Rajwinder Singh (Wolters Kluwer Medknow Publications, 2019)
Accidental trauma involving the eye may necessitate surgical removal of the eye ball. Immediate management should consider future prosthetic rehabilitation. Insertion of eye ball implant after enucleation or evisceration preserves socket anatomy, maintains sulcus and fornix which ensures proper retention of ocular prosthesis in future. Placement of intraorbital ball implant also reduces the weight as well as enhances motility of the prosthesis, thus imparting life-like appearance. Custom-made acrylic prosthesis has been shown to deliver superior functional and esthetic result. Exact positioning of the iris disc on a custom-made scleral blank is critical from esthetic point of view. This clinical report describes prosthetic rehabilitation of an anophthalmic socket where intraorbital ball implant was inserted during evisceration. Custom-made acrylic ocular prosthesis with a prefabricated iris button was used. Here, digital photography and a specially fabricated spectacle gridded with mm scale were used for positioning iris button on the ocular prosthesis. These two methods of centration of iris button may be used to reduce chairside time and increase patient cooperation with a positive clinical outcome.